MONITORING TEKANAN DAN KONTROL KEBOCORAN GAS LPG BERBASIS INTERNET OF THINGS - Vivi Vonny; Hasbullah Hasbullah; Eko Sulistyo; Aan Febriansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
Early warning of LPG gas leaks is currently not maximized. So that it can cause a fire when a gas leak occurs and the user cannot monitor it remotely. So we need control equipment that can detect gas leaks and gas pressure that can be monitored directly via a smartphone. The purpose of making this control is to release the regulator from the gas cylinder automatically in the event of an LPG gas leak and the user can monitor the LPG gas pressure directly via a smartphone. Making gas leak control using gas sensors and pressure sensors placed near the regulator, the hazard level is determined using the fuzzy logic method and displayed on the smartphone using the Blynk application. The results of the gas sensor accuracy test using a gas lighter with an accuracy of 0.46% and the sensor is able to read gas leaks with a maximum distance of 16 cm from the leak point. Gas pressure testing uses a gas pressure sensor using different gas cylinders with an accuracy of 0.19%. From the test results by applying Mamdani fuzzy logic into 3 membership functions, namely the membership functions AMAN, WASPADA and DANGER.